An effective hydroxylation route for a highly sensitive glucose sensor using APTES/GOx functionalized AlGaN/GaN high electron mobility transistor. Issue 19 (18th March 2020) - Liu, Jun; Zhang, Heqiu; Xue, Dongyang; Ahmad, Aqrab ul; Xia, Xiaochuan; Liu, Yang; Huang, Huishi; Guo, Wenping; Liang, Hongwei
Abstract : A highly sensitive glucose sensor based on AlGaN/GaN high electron mobility transistor (HEMT) has been fabricated. Abstract : A highly sensitive glucose sensor based on AlGaN/GaN high electron mobility transistor (HEMT) has been fabricated. The hydroxyl groups on the GaN surface were achieved by the decomposition of hydrogen peroxide solution (H2 O2 ) under UV irradiation for the production of hydroxyl radicals. The self-assembled monolayers (SAMs) of 3-aminopropyltriethoxysilane (APTES) with terminal amino groups formed on the hydroxylation surface were used as substrates for glucose oxidase (GOx) immobilization. The chemical groups on the GaN surface after hydroxylation were confirmed by X-ray photoelectron spectroscopy. From the analysis of current signals, the biosensor constructed with APTES/GOx exhibited good current response to glucose over a linear range from 10 to 100 µM with a sensitivity of 3.15 × 10 4 µA mM −1 cm −2 and a detection limit of 10 nM. Meanwhile, the anticipated idea about the hydroxylation of GaN surface, can be an efficient approach for the design of AlGaN/GaN HEMT based biosensors in the future.